Mercury records covering the past 90 000 years from lakes Prespa and Ohrid, SE Europe - Paine, AR; Fendley, IM; Frieling, J; Mather, TA; Lacey, JH; Wagner, B; Robinson, SA; Pyle, DM; Francke, A; Them II, TR; Panagiotopoulos, K (European Geosciences Union, 2024)
The element mercury (Hg) is a key pollutant, and much insight has been gained by studying the present-day Hg cycle. However, many important processes within this cycle operate on timescales responsive to centennial- to millennial-scale environmental variability, highlighting the importance of also investigating the longer-term Hg records in sedimentary archives. To this end, we here explore the timing, magnitude, and expression of Hg signals retained in sediments over the past ∼ 90 kyr from two lakes, linked by a subterranean karst system: Lake Prespa (Greece, North Macedonia, and Albania) and Lake Ohrid (North Macedonia and Albania). Results suggest that Hg fluctuations are largely independent of variability in common host phases in each lake, and the recorded sedimentary Hg signals show distinct differences first during the Late Pleistocene (Marine Isotope Stages 2–5). The Hg signals in Lake Prespa sediments highlight an abrupt, short-lived peak in Hg accumulation coinciding with local deglaciation. In contrast, Lake Ohrid shows a broader interval with enhanced Hg accumulation and, superimposed, a series of low-amplitude oscillations in Hg concentration peaking during the Last Glacial Maximum, which may result from elevated clastic inputs. Divergent Hg signals are also recorded during the Early and Middle Holocene (Marine Isotope Stage 1). Here, Lake Prespa sediments show a series of large Hg peaks, while Lake Ohrid sediments show a progression to lower Hg values. Since ∼ 3 ka, anthropogenic influences overwhelm local fluxes in both lakes. The lack of coherence in Hg accumulation between the two lakes suggests that, in the absence of an exceptional perturbation, local differences in sediment composition, lake structure, Hg sources, and water balance all influence the local Hg cycle and determine the extent to which Hg signals reflect local- or global-scale environmental changes.